META ANALISIS PENGARUH MODEL PEMBELAJARAN JOYFUL LEARNING TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Salamah, Umi; Taufiq, Muhammad; Akhwani, Akhwani; Nafi’ah, Nafi’ah (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
The purpose of this study was to analyze the effect before and after the use of the Joyful Learning learning model. The method used is a meta-analysis method. The data obtained by searching online journals through google scholar with the keyword Joyful Learning, primary school learning outcomes. From the results of the research, there were 5 articles. The results showed that using the Joyful Learning model could improve student learning outcomes with an average result before the Joyful Learning model was given of 59.34 and increased after being given the Joyful Learning model of 70.36. From statistical calculations, it shows that the Sig. (2-tailed) (0.025) <(0.05). So it shows that H0 is rejected and H1 is accepted because Sig <0.05.